Measuring Efficiency of Selected Indian Commercial Banks : A DEA-Based MPI Approach - Kumar, Vijyapu Prasanna; Kar, Sujata (Indian Journal of Finance, 2021)
This paper attempted to measure the change in productivity of 19 commercial banks in India from 2013 – 2018. The nature of efficiency and productivity change was investigated with the help of the output - oriented Malmquist Productivity Index (MPI) through intermediation approach. The MPI has components that are used in performance measurements, such as changes in technology efficiency, technical efficiency, pure technical efficiency, scale efficiency, and total factor productivity. The results of the study demonstrated that Ratnakar Bank Limited had the highest MPI score against both the technological change and total factor productivity change ; whereas, State Bank of India and Punjab National Bank had the lowest MPI scores. Overall, the private sector banks were found to be more productive compared to the public sector banks for the period under consideration.